2007
DOI: 10.1002/app.25778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanoparticles on the density reduction and cell morphology of extruded metallocene polyethylene/wood fiber nanocomposites

Abstract: This article investigates the effects of nanoparticles on cell morphology and foam expansion in the extrusion foaming of metallocene polyethylene/wood fiber nanocomposites with a chemical blowing agent. The results indicate that the addition of clay generally reduces the cell size, increases the cell density, and facilitates foam expansion. Furthermore, the foam material with added clay shows good char formation when it is burned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 19 publications
1
55
0
1
Order By: Relevance
“…This could be because the finest WF enhanced the cell nucleation. A very fine-celled structure, with the majority of cells smaller than 50 lm, and a desired density range of 0.4-0.8 g/cm 3 was successfully obtained. The small-sized WF composites also have a higher complex viscosity, as the small WF particles offer a larger surface area for particle-particle and particlematrix interactions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This could be because the finest WF enhanced the cell nucleation. A very fine-celled structure, with the majority of cells smaller than 50 lm, and a desired density range of 0.4-0.8 g/cm 3 was successfully obtained. The small-sized WF composites also have a higher complex viscosity, as the small WF particles offer a larger surface area for particle-particle and particlematrix interactions.…”
Section: Discussionmentioning
confidence: 91%
“…1 However, their potential applications have been limited because of their low impact strength and high density compared to natural wood. Foaming WPC by either chemical blowing agents (CBA), [2][3][4][5] physical blowing agents (PBA), [6][7][8][9][10][11] or by stretching, 12,13 can decrease the density, reduce material cost, and improve their mechanical properties such as impact strength and tensile strength. Producing a uniform fine-celled or microcellular structure in WPC has been demonstrated to be extremely effective at improving their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of nanoparticles [e.g., nanoclay and carbon nanotubes (CNTs)] may be one of the ways to decrease cell size and achieve more uniform cells in WPCs. It has been reported that the addition of clay improved the cell morphology of foamed WPCs [7, 8]. However, few publications are available on the effect of multi‐walled carbon nanotubes (MWCNTs) on the foaming behavior of WPCs, and the potential of CNTs as nucleating agents for WPCs has not been fully realized.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these works are about foaming using supercritical fluids, [15][16][17][18][19][20][21][22][23] only a few of them are foaming using chemical foaming agents. [24][25][26][27][28] In our previous study, 29 we prepared biodegradable PCL foams using chemical foaming method and the structure-property relationship of PCL foams were studied. However, the applications of PCL foams are limited by the relatively poor mechanical properties and high production cost of the PCL matrix.…”
Section: Introductionmentioning
confidence: 99%